Effect of Microwave Irradiation on Synthesis of Phenol from Benzene Over Activated Carbon as Supported Catalysts - Liu, T.; Hou, J.H. (Asian Journal of Chemistry, 2014)
Hydroxylation of benzene to phenol with hydrogen peroxide over catalysts prepared by Fe(III), Cu(II), Co(II) impregnated on activated carbon was examined at room temperature under microwave irradiation. The Fe(III)/activated carbon catalyst gave the highest conversion and yield. The effects of various reaction parameters, such as the different solvents, the amount of solvent, the amount of catalyst, the amount of hydrogen peroxide and the reaction time on the yield of phenol, were studied to obtain the optimal reaction conditions for phenol formation under microwave irradiation. A benzene conversion of 28.9 % with a selectivity of 100 % was obtained when the 5 % loading amount of Fe(III) under optimized conditions.